Female Sexual Dysfunction: A Reddit Analysis of the Lost Libido. (1st August 2022) - Belcher, R; Sim, D; Meykler, M; Owens-Walton, J; Hassan, N; Rubin, R; Malik, R
ABSTRACT: Introduction: Female sexual dysfunction (FSD) encompasses difficulties with sexual desire, libido, arousal, orgasm and pain. These medical problems are often multi-factorial in origin and can cause significant distress to patients. FSD can be a particularly sensitive topic to discuss, and patients may not feel comfortable seeking help from healthcare providers. Objective: We aimed to evaluate the experience of women with low libido on Reddit, an anonymous forum-based platform that allows users to interact with a global audience, to gain a better understanding of how FSD affects patients. Methods: The subreddit "TwoXChromosomes" was queried using the Reddit Application Programming Interface (API) for posts using the keywords "libido" and "sex drive". Posts that were deleted, archived or unrelated to themes of FSD were excluded. Threads were qualitatively analyzed using the grounded theory approach. Five independent researchers read and coded each thread identifying dominant themes and emergent concepts. Results: Qualitative analysis of eighty five threads and approximately 2, 900 comments resulted in 5 preliminary themes: medications effects on libido, the interplay between libido and relationships, the purpose of sex, the psychological impact of FSD, and challenges with healthcare. Users frequently described a decrease in libido secondary to medications, particularly antidepressants and hormonal birth control, with resolution upon stopping or switching medications. Users with low libido also reported positive sexual/romantic relationships, suggesting that their sexual dysfunction is unrelated to their partner; however, many posters discussed the challenges navigating a relationship with mismatched libido. Users discussed the role sex plays in relationships, whether as way to develop intimacy between partners or to achieve orgasm. Additionally, users described feeling distressed and anxious about their FSD. Finally, posters expressed dissatisfaction with healthcare providers and the healthcare system when trying to address their concerns. Conclusions: Reddit serves as a resource and support group for users experiencing FSD. Posters share their experiences with low libido and its effect on their relationships. Many women discussed various psychological consequences of FSD, which suggests that a patient-centered approach is critical in managing FSD. Similarly, our research demonstrates a gap between provider based sexual health care concerns and patient concerns, emphasizing the need for greater awareness of and improved provider education about FSD. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Sprout (Raliegh, NC), Absorption Pharmaceuticals, Urovant Sciences, Inc.